REVIEW OF MANAGEMENT INFORMATION SYSTEMS USING EXPERT SYSTEMS IN INTERNAL CONTROL FOR INDONESIA'S BUREAUCRATIC REFORM - Sinulingga, Minan; Djati, Sundring Pantja; Thamrin, Suyono; Saragih, Herlina Juni Risma; Wijaya, Hendy Risdianto (Jurnal Pilar Nusa Mandiri, 2023)
Technological developments are driving changes in bureaucratic reform, through Presidential Regulation No. 81 of 2020 which targets that by 2025 a system of oversight and accountability will be created to create a government with high integrity. Increasing SPBE (Electronic Based Government System) by implementing MIS (Management Information System) is one of the keys to achieving this target. This study aims to examine the use of MIS for internal control (SIMWAS) using an expert system, especially for internal audits associated with bureaucratic reform in Indonesia. This research method uses a Systematic Literature Review (SLR) to find suitable articles from various sources from 2015 to 2021 and conducts a Trend Analysis of the SLR results and a total of 31 articles to find research trends. The results of this study indicate that there is still no research related to supervision and internal auditors associated with bureaucratic reform and performance. Research on internal audits to improve performance using SIMWAS using an expert system has also not been done yet. This research can be developed using artificial intelligence to evaluate, predict and improve the performance of internal auditors that impact organizational performance. This study shows that the use of MIS for internal control using an expert system for internal audit still needs to be improved to support bureaucratic reform, especially the increase in SPBE.